Privid pravne konstrukcije - Obreza, Timotej (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2024)
Lawyers tend to think about their work in a similar manner. Through the patterns of knowledge acquired during their education and subsequent work in a particular area of law, they adopt an established cognitive scheme. This paper argues that such a cognitive scheme can be understood as a phantasm of a legal construction laid out before the eyes of lawyers. While "phantasm" refers to the fact that this image is indeed imaginar - albeit necessary - "legal construction" refers both to the conception (the result) and the design (the creative process) of the legal sphere. Through this phantasm, lawyers not only secure access to a specific truth by which they learn and shape the world of law; they also gain the privilege of monopolising and monetising this field of knowledge. The key to this is the learned cognitive method, which forms the "frame" of legal construction and consists of the unit, technique and virtue of legal communicability. The paper briefly illustrates these three elements and highlights some of the shortcomings of legal reasoning. It then identifies methodological pluralism as a crucial precondition for a more comprehensive understanding of the world around us - a cognitive synthesis. The central thread, which is fatal to the idea of the phantasm of legal construction and which the paper adopts, concerns accepting the importance of legal work on the one hand, and the responsible use of the privilege of legal knowledge on the other.
Keywords: legal construction; legal knowledge; methodological pluralism; metodološki pluralizem; odgovoren monopol znanja; phantasm; pravna konstrukcija; pravna vednost; privid; responsible knowledge monopoly